Alternative Energies and Efficiency Evaluation - Wakil Shahzad, Muhammad; Sultan, Muhammad; Dala, Laurent; Bin Xu, Ben; Jiang, Yinzhu (IntechOpen, 2022)
Global energy demand is expected to grow 47% by 2050, with oil remaining the number one source of energy. Renewables make up 27% of the global energy mix, as predicted by the International Energy Agency (IEA). To achieve IEA's 2050 Net Zero targets, the electricity sector needs to reduce global emissions by nearly three-quarters. Even though renewables installations are expanding quickly, there is not enough to satisfy a strong rebound in global electricity demand. This will result in a sharp rise in the use of fossil fuel electricity generation that risks pushing carbon dioxide emissions. This book presents a comprehensive overview of energy efficiency, alternative energy resources, and process optimization for future sustainability.